Chapter 10 Moral Conflict in the Minimally Conscious State - Shepherd, Joshua (Oxford University Press, 2016)
In the next section, I sketch a view in which the possession of phenomenal consciousness (henceforth: "consciousness") is necessary for possession of (positive or negative degrees of) subjective well-being. It would seem that the possession of consciousness supplies caregivers reason to enhance the well-being of MCS patients. Unfortunately, as I discuss next, matters are complicated by a certain kind of moral conflict that arises in decision-making situations regarding MCS patient care. In many cases, it seems difficult, and perhaps impossible, to respect an MCS patient's autonomy-as embodied in her autonomously expressed prior wishes or in the wishes she would presently autonomously express were she competent to do so-while promoting the well-being she presently enjoys and will plausibly enjoy in the future. Later, I consider views according to which the moral conflict is only apparent, because considerations of autonomy trump considerations of well-being (or vice-versa). I argue that neither view is satisfying: We are left with genuine moral conflict. However, consideration of these views is salutary, because their weaknesses motivate a mixed view in which considerations of both autonomy and well-being should in many cases be weighed against each other, as well as other relevant moral considerations (e.g., considerations of distributive justice). In the final section, I draw four practical conclusions.